Secondary Packaging Performance Assessment Based on Mechanical Damage Resistance Using Drop Testing and Forensic Packaging Methods at CV. Mubarokfood Cipta Delicia - Saputra, Rheznandya Gaffi Rangga; Naziha, Thalia (Agroindustrial Journal, 2025)
Distribution is a process that could decrease the quality of food products biologically, chemically, and physically. Therefore, food packaging plays a crucial role in extending the shelf life and maintaining the quality and safety of food products. This research aims to gather evidence on packaging damage data that can be used to evaluate the effectiveness of product packaging, considering its durability and ability to protect products, and to understand the impact of packaging damage on product quality. Data collection was carried out by observing the packaging chosen as a research sample, specifically 9 Mubarok’s Jenang secondary slop packaging. Each package contains 4 Jenang inside, so there were 36 Mubarok’s Jenang in total. The author also conducted interviews to obtain relevant information about the topics in this section, including packaging, quality control, and the purchasing division. Drop testing and forensic packaging methods were performed manually by dropping the item from a fixed height onto a solid, hard, and flat surface, as specified in ISO 2248:1985. Based on the research result after testing from three variations of drop height (50 cm, 100 cm, 150 cm) with each height containing three sample packages, all of the packaging is in a “good” category, which is proven by the value of bruise susceptibility parameter is very low, packaging damage is in the light category, and the product’s primary packaging is still tightly sealed so that it can maintain the quality and shelf life of Jenang during the retention period. Then, consecutively, the average values and their deviations for the bruise susceptibility of the packaging at heights of 50 cm, 100 cm, and 150 cm are 0.0549 cm³/Joule, 0.0735 ± 0.0164 cm³/Joule, and 0.0699 ± 0.0214 cm³/Joule.